Identifying the spatial pattern, driving factors and potential human health risks of nitrate and fluoride enriched groundwater of Ordos Basin, Northwest China. (20th November 2022) - Qu, Shen; Duan, Limin; Shi, Zheming; Mao, Hairu; Wang, Guangcai; Liu, Tingxi; Yu, Ruihong; Peng, Xiaohong
Abstract: While the identification of the spatial patterns of fluoride (F − ) and nitrate (NO3 − ) is important for groundwater management, these patterns remain poorly understood in the Ordos Basin. A total of 107 groundwater samples collected from phreatic aquifers were divided into three clusters using the self-organizing map (SOM). Cluster I, Cluster II and Cluster III represented the contaminated groundwater with different type and degree of pollution. On this basis, factor analysis (FA), together with classical hydrochemical diagrams reflected the major factors regulating the spatial characteristics of groundwater F − and NO3 − . Firstly, water-rock interaction (carbonate precipitation, fluorite dissolution, and cation exchange) and evaporation were responsible for high groundwater NO3 −, F −, hardness, and salinity. Secondly, anthropogenic inputs (agricultural activities and sewage) also contributed to high groundwater NO3 − and F − . Finally, the universal alkaline environment could regulate groundwater NO3 − and F − . Additionally, 68.22%, 37.38%, and 33.64% of samples showed higher total non-carcinogenic risk (HITotal > 1) for children, adult females, and adult males, respectively. Overall, the worst NO3 − and F − contamination and health risks were evident in the western part of the Ordos Basin. The results of this study can contribute to the sustainable development of groundwater and to the protection of public health in the Ordos Basin.